A Fast Geometric Optics-Based Design Approach for Dielectric Rod Antennas - Jingping Liu; Safieddin Safavi-Naeini; Ying Wang; Aidin Taeb (International Journal of Antennas and Propagation)
A simple and effective dielectric rod antenna design approach based on geometric optics and modal analysis is presented. The tapered antennas from microwave to terahertz can be readily designed with the equations presented in this paper. The radius of antenna is determined by the desired traveling wave mode inside the antenna. The field inside the antenna consists of the fundamental mode and the second mode. For the end-fire operation, there is only the fundamental mode. The length of the antenna is designed based on geometric optics theory so that most of the traveling wave will be converted to the radiating field towards the output plane, avoiding reflection inside the antenna. Such antennas can achieve wide bandwidth. The gain increases with the length of the antenna as long as the diameters and length satisfy the conditions given in this paper. A number of antenna design examples with high gain and wide bandwidth are presented. The measurement results of a 130 GHz rectangular antenna with a length of 4λ show a bandwidth of 60 GHz and a gain of 12 dB.